2015
DOI: 10.12968/johv.2015.3.4.216
|View full text |Cite
|
Sign up to set email alerts
|

Factors that influence commitment to breastfeeding: A pilot study

Abstract: Background: Only 1% of mothers in the UK meet the World Health Organization recommendation of exclusive breastfeeding for the first 6 months. Understanding what helps UK mothers to commit to exclusive breastfeeding could help shape the promotion and support of breastfeeding. Objective: To investigate the experiences of mothers who are fulfilling this recommendation, by considering their initial motivations, the barriers they faced and effective coping strategies. Design: Seven mothers (average age 30.2 years) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…This theory is supported by Hauck and Irurita (2003) who found that once mothers had made the decision to wean their baby from the breast, they persevered even when faced with their baby's opposition. Studies previously describe features of maternal character/personality including determination, perseverance and self‐efficacy as factors in overcoming breastfeeding challenges and increasing breastfeeding duration (Brown, 2014; Burns, Schmied, Sheehan, & Fenwick, 2010; Hegney, Fallon, & O'Brien, 2008; Jardine, McLellan, & Dombrowski, 2017; Ricotti, Apekey, & Gatenby, 2015; Williamson, Leeming, Lyttle, & Johnson, 2012). From this, it could be construed that maternal determination being an implicit factor in eventual acceptance is a plausible one.…”
Section: Discussionmentioning
confidence: 99%
“…This theory is supported by Hauck and Irurita (2003) who found that once mothers had made the decision to wean their baby from the breast, they persevered even when faced with their baby's opposition. Studies previously describe features of maternal character/personality including determination, perseverance and self‐efficacy as factors in overcoming breastfeeding challenges and increasing breastfeeding duration (Brown, 2014; Burns, Schmied, Sheehan, & Fenwick, 2010; Hegney, Fallon, & O'Brien, 2008; Jardine, McLellan, & Dombrowski, 2017; Ricotti, Apekey, & Gatenby, 2015; Williamson, Leeming, Lyttle, & Johnson, 2012). From this, it could be construed that maternal determination being an implicit factor in eventual acceptance is a plausible one.…”
Section: Discussionmentioning
confidence: 99%